48 Evaluation of Antimicrobial Activities of Phytophenols Against Bacterial Pathogens That Cause Liver Abscesses in Feedlot Cattle. (7th May 2021) - Roubicek, Cierra; Amachawadi, Raghavendra G; Nagaraja, T G; Li, Yonghui; Wang, Jinrong; Salih, Harith M
Abstract: Liver abscesses occur in finishing cattle fed high-grain, low-roughage diets. Cattle with abscessed livers do not show any clinical signs and are detected only at slaughter. Liver abscesses, which account for 67% of all liver abnormalities in cattle slaughtered in the United States, are of major economic concern to the beef industry. Fusobacterium necrophorum, Trueperella pyogenes, and Salmonella enterica, particularly the serotype Lubbock, are the main etiologic agents. Currently, the control of liver abscesses is based on in-feed use of antibiotics. The emergence and dissemination of antimicrobial resistance to antibiotics use in animals is a public health concern. Plant-based phenolic compounds, called phytophenols, are known to have antimicrobial properties. Our objectives were to evaluate antimicrobial activities of phytophenols on the liver abscess bacterial pathogens. Phytophenols extracted from rosemary, green tea, grapeseed, organic goji berry, and green coffee were selected for testing. The phytophenols were extracted using 75% aqueous acetone and total phenolic content was determined by a spectrophotometric analysis. Bacteria were cultured in Mueller-Hinton broth (S. Lubbock and T. pyogenes) or anaerobic brain-heart infusion broth (F. necrophorum with and without phytophenols, at 6, 12, 24, and 48 hours and bacterial concentrations were determined. If phytophenol was inhibitory, a micro-broth dilution method was used to quantify the inhibition. Phytophenols from green tea, grape seed, and rosemary inhibited T. pyogenes. Further studies are ongoing to investigate different concentrations of phenolic compounds on the pathogens. Phytophenols that inhibit the pathogens may have the potential to be used as feed additives to prevent liver abscesses.